THE POTENTIAL OF PRINCE DIPONEGORO MUSEUM AS A LEARNING RESOURCE FOR SMP SCHOOL SOCIAL SCIENCES - Putri, Raudya Setya Wismoko; Suprihatiningsih, Suprihatiningsih; Septiani, Endah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
This study aims to describe what it is about the potential of the Prince Diponegoro museum as a social studies learning resource in high schools. This study uses a type of qualitative research whose aim is to understand the phenomena experienced by research subjects using naturalistic methods with data obtained in the field naturally, as they are, not manipulated, and without being influenced intentionally. case studies with various data collection techniques. The results showed that the Prince Diponegoro Museum, which is located in Tegalrejo Village, Tegalrejo District, Yogyakarta City, is suitable to be used as an alternative source of social studies learning in secondary schools, based on the results of observations and interviews in the field with the management of the Prince Diponegoro Museum and junior high school teachers who had visiting the Prince Diponegoro Museum Diponegoro Museum, according to them the collection of the Prince Diponegoro Museum is worthy of being used as a learning resource, especially social studies subjects at the junior high school level. The majority of the collections have great potential when viewed from the weight of the collection, not too heavy and not too light, also for junior high school level learning.